Aneurisma gigante de Arteria Cerebral Media: Trapping y By-Pass - Rubino, Pablo; Gallardo, Federico; Martin, Clara; Diaz, Juan Francisco; Orellana, Marcelo; Lambre, Jorge (Revista Argentina de Neurocirugía, 2020)
Objective: To present the surgical resolution of a giant aneurysm of the middle cerebral artery using Trapping and By-Pass technique. Introduction: The 5-year mortality rate of patients with giant aneurysms is 80%. Due to its wide neck, sometimes-direct clipping is not possible, requiring trapping of the aneu-rysm followed by bypass revascularization. Material and Method: Clinical history data and intraoperative video images of a pa-tient with a giant aneurysm of the middle cerebral artery were analyzed. Results: The superficial temporal artery and its branches were identified through a Pterional approach. After careful aneurysm dissection, primary clipping was attempted, but the flow in the temporal branch of the middle cerebral artery was compromised. Due to its wide neck, associated atherosclerosis and intrasaccular thrombus, an Extra-intracranial bypass was performed from superficial temporal artery to temporal branch of middle cerebral artery, followed by trapping technique of the aneurysm. Then the aneu-rysm was sectioned and the thrombus contained inside was removed, decreasing the mass effect exerted by it. A Doppler probe was used to corroborate bypass permeability, as well as 3D reconstruction angiotomography during the postoperative period. The pa-tient was discharged without associated complications and a modified Rankin scale of 1. Conclusion: Surgical resolution of a giant middle cerebral artery aneurysm was present-ed by Trapping technique followed by extra-intra-cranial temporo-Silvian bypass.